Design of model rocket with integrated flight control system - Kadlec, Ondřej; Walla, Petr (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
This article is describing design and construction of rocket model with solid propellant engine, which communicates in real-time with server. Purpose of this rocket is to engage in vertical flight and afterwards safely return back to the ground, while sending data and recieving orders. In scope of this thesis we developed desktop application versatile in use for controlling flights of model rockets.
Keywords: rocket; solid propellant rocket motor; rocket recovery; flight software; ground control